2021
DOI: 10.1590/acb360106
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hemostatic efficacy of topical Ankaferd Blood Stopper on heparinized and nonheparinized rats in bleeding related to liver injury

Abstract: Purpose: In this study, hemostatic efficacy of Ankaferd Blood Stopper (ABS), a new generation hemostatic agent, was compared in the presence of heparin effect. Methods: Forty-eight Wistar albino rats were divided into two main groups as heparinized and nonheparinized, and these two main groupswere divided into six subgroups as control, Surgicel and ABS (n = 8). Grade 2 liver injury was performed on rats as standard. All groups were compared in terms of weight, laceratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In the study groups that suffered second-degree liver damage, it was reported that heparinizing could be useful to ABS in stop bleeding by e ABS hemostatic effect in heparinized group as soon as possible. [19] In a study conducted by Adams GL et al using the pig model, hemostatic effects were compared using Gelfoam plus saline and Gelfoam plus human thrombin in liver laser hemorrhage. Gelfoam plus human thrombin was observed to provide better control of bleeding compared to Gelfoam plus saline.…”
Section: Discussionmentioning
confidence: 99%
“…In the study groups that suffered second-degree liver damage, it was reported that heparinizing could be useful to ABS in stop bleeding by e ABS hemostatic effect in heparinized group as soon as possible. [19] In a study conducted by Adams GL et al using the pig model, hemostatic effects were compared using Gelfoam plus saline and Gelfoam plus human thrombin in liver laser hemorrhage. Gelfoam plus human thrombin was observed to provide better control of bleeding compared to Gelfoam plus saline.…”
Section: Discussionmentioning
confidence: 99%